2001
DOI: 10.4049/jimmunol.166.8.4968
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanticity of α2-Macroglobulin, an Independent Ligand for the Heat Shock Protein Receptor CD91

Abstract: We recently have identified CD91 as a receptor for the heat shock protein gp96. CD91 was identified initially as a receptor for α2-macroglobulin (α2M). Gp96 and α2M are both ligands for CD91. Because gp96-chaperoned peptides can prime CD8+ T cell responses and are re-presented by APCs, we tested α2M for similar properties. Our studies show that α2M binds peptides in vitro and that the peptides, chaperoned by α2M, efficiently prime peptide-specific CD8+ T cell responses in mice immunized with α2M-peptide comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 16 publications
3
49
0
1
Order By: Relevance
“…Moreover, our results showing that ␣ 2 M present in RASF may be captured by CD91 (Fig. 6A) indicate that ␣ 2 M, which displays the capacity to chaperone Ags into DCs for T cell cross-priming (22), also contributes to the RA cross-priming process. Future studies might include determining the effects of specific inhibitors of hsp70 such as deosyspergualin (34) on hsp/DC-mediated crosspriming events in RA and other autoimmune diseases, assessing the interactions of other hsp family members, such as Ig H chain binding protein, and characterizing ␣ 2 M/DC interactions in the RA joint.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, our results showing that ␣ 2 M present in RASF may be captured by CD91 (Fig. 6A) indicate that ␣ 2 M, which displays the capacity to chaperone Ags into DCs for T cell cross-priming (22), also contributes to the RA cross-priming process. Future studies might include determining the effects of specific inhibitors of hsp70 such as deosyspergualin (34) on hsp/DC-mediated crosspriming events in RA and other autoimmune diseases, assessing the interactions of other hsp family members, such as Ig H chain binding protein, and characterizing ␣ 2 M/DC interactions in the RA joint.…”
Section: Discussionmentioning
confidence: 91%
“…The binding to hydrophobic molecules does not inhibit the trapping of proteases and is not known to be associated with any conformational changes (Barrett 1981). Previous work has indicated that α 2 M-polypeptide complexes are immunogenic (Chu and Pizzo 1993;Binder et al, 2001). α 2 M bound peptides are internalised by LRP and fragments of the peptide are subsequently re-presented on the cell surface.…”
Section: Haptoglobinmentioning
confidence: 99%
“…It is interesting to note that α2-macroglobulin, the originally described ligand for CD91, is also able to channel exogenous antigens into the endogenous pathway of antigen presentation via the same receptor (Ref. 157).…”
Section: Tumour Immunitymentioning
confidence: 99%